2006
DOI: 10.1007/s10681-006-9114-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Phytohormones and Male Sterility in Thermo-Photo-Sensitive Genic Male Sterile (TGMS) Wheat

Abstract: Fertility alternation normally occurs in a novel type of thermo-photo-sensitive genic male sterile (TGMS) wheat whose recessive genes in the nucleus are expressed as virtually complete sterility under lower temperature and shorter daylight conditions, but as normal fertility under higher temperature and longer daylight conditions during the developmental period from meiosis of pollen mother cells (PMCs) to the early mononucleate stage of microsporogenesis. In order to provide more information about the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…When we investigated TaMIPS-B over-expressing rice transgenic at reproductive stage and we observed a reduced in seed setting rate with maximum reduction in L2 which had highest level of MI. During heat stress, rate of evolution of ethylene in heat sensitive variety is higher than tolerant one, which is correlated to higher male sterility and results in reduced grain yield 31,32 . Decrease in seed setting rate in over-expressing TaMIPS-B transgenic might be because of over-production of ethylene which results in reduced fertility.…”
Section: Discussionmentioning
confidence: 99%
“…When we investigated TaMIPS-B over-expressing rice transgenic at reproductive stage and we observed a reduced in seed setting rate with maximum reduction in L2 which had highest level of MI. During heat stress, rate of evolution of ethylene in heat sensitive variety is higher than tolerant one, which is correlated to higher male sterility and results in reduced grain yield 31,32 . Decrease in seed setting rate in over-expressing TaMIPS-B transgenic might be because of over-production of ethylene which results in reduced fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf tissue of Asakura-sanshoo (0.2 g) was frozen in liquid nitrogen and then ground to a fine powder. Indole acetic acid (IAA), trans -zeatin ( trans- Z), and trans -zeatin riboside ( trans- ZR) were extracted and quantified using the methods described by Zhang et al ( 2006 ) and Wang and Xiao ( 2009 ), with some modifications. The extracts in the vials were injected into an HPLC equipped with a YWG-C 18 stainless-steel column (4.6 mm × 250 mm, 5 μm; Waters, Milford, MA, USA), coupled to an ultraviolet detector (G1314A; Agilent, Palo Alto, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The main network disappeared, and only 2 sub-networks of indole metabolism and coenzyme A biosynthesis metabolism were kept 2000; Pan et al 2014). IAA content in anthers of sterile line was about 80% of fertile line in wheat male sterile line C49S and BNS (Zhang et al 2006(Zhang et al , 2013b(Zhang et al , 2016. Based on the transcriptional profiles, we found that IAA metabolism was a typical differential metabolic pathway in network between anthers and young panicles tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A series of two-line system male sterile lines were found and applied in recent 20 years in China (Li et al 2006(Li et al , 2009(Li et al , 2011aZhang et al 2006;Zhao 2010). BNS is a thermo-sensitive genic male sterile line with good sterility and good self-conversion.…”
Section: Introductionmentioning
confidence: 99%